2018
DOI: 10.1080/17550874.2019.1610912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dark septate endophytes on tomato growth and nutrient uptake

Abstract: Background: Dark septate endophytes (DSEs) represent a form-group of ascomycetous fungi that inhabit the roots of a wide range of plant species, but our knowledge on their interaction with the host plants is still limited. Aims: This study was conducted to examine the effect of DSEs on the nutrition and growth of tomato (Solanum lycopersicum) in order to assess their potential application in horticultural plant production. Methods: The capacity of two model DSE species, Periconia macrospinosa and Cadophora sp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…According to Ban et al [47], melanin, an essential antioxidant, accumulates in fungal cell walls when in contact with heavy metals to protect root cells against heavy metals. DSE colonization has also been shown to promote plant growth and allow the utilization of nutrients from organic sources and nutrient uptake in poor soils [48].…”
Section: Discussionmentioning
confidence: 99%
“…According to Ban et al [47], melanin, an essential antioxidant, accumulates in fungal cell walls when in contact with heavy metals to protect root cells against heavy metals. DSE colonization has also been shown to promote plant growth and allow the utilization of nutrients from organic sources and nutrient uptake in poor soils [48].…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects of DSEs on plant growth have been mainly linked to improved plant nutrition (Haselwandter and Read 1982; Jumpponen, Mattson and Trappe 1998; Newsham 2000; Yakti et al . 2018; Yakti et al . 2019), for example, DSEs had significant effects on plant biomass when N was supplied in organic form (Newsham 2011) pointing out to their ability to solubilize nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Other important aspects of endophyte effects on plants relate to nutrient uptake and use, and biocontrol activity (Murphy et al 2014;Høyer et al 2019). Yakti et al (2018) have shown that two model Dark Septate Endophytes (DSE) improved nitrogen uptake in tomato from organic sources and suggested that this might be due to nutrient mobilisation rather than hyphal transport to the plant. Two of the contributions to this SI highlight the biocontrol activity…”
Section: Ecologymentioning
confidence: 99%